The Impact of Deceptive Advertising and Moral Violation on Negative Word of Mouth Mediating role of Brand Hate - Ansar Abbas; Amir Hussain Shar; Mumtaz Ali Junejo (Review Journal of Social Psychology & Social Works, 2024)
The purpose of this paper is to investigate the effects of consumer deceptive Advertising and moral violations by brands on to brand hate and how brand hate results in spreading negative word of mouth. Primary data was collected through questionnaires. To know the impact of the variables 150 questionnaires were distributed among university students of Central Punjab and Islamabad region. Results show that deceptive advertising directly impacts negative word of mouth while moral violations have no impact in this study context. Brand hate mediates the relationship between deceptive advertising and negative word of mouth. This study is helpful for clothing line brands of Pakistan in order to capture consumers by giving quality and try to avoid negative experiences of consumers so that consumers do not start hating the brand and which may not result in spreading negative word of mouth from consumer perspective.